Human pressures exacerbate the impacts of hydroclimatic extremes on river greenhouse gas emissions - Diego G. Panique-Casso; Peter Goethals; Long Ho (Journal of Hydrology, 2026)

Urbanisation impacts avian biodiversity on stream ecosystems – insights from a large geographical scale - Ana Cláudia Norte; Marcos Dias; Ana Raquel Calapez; Janine Pereira da Silva; Sónia R.Q. Serra; Silje Havrevold Henni; May-Linn B. Mørch; Anne Moen; Rayan Bouchali; Adeline Loyau; Dirk S. Schmeller; Peter Goethals; et al. (Journal of Environmental Management, 2026)

Quantifying global population exposure to compound drought/wet and hot events using multiple indicators - Tao Li; Fengjiao Song; Andrée De Cock; Philippe De Maeyer; Jiayu Bao; Min Liu; Xiaolin Chen; Naibi Sulei; Anming Bao; Peter Goethals (Global and Planetary Change, 2026)

DNA methylation as a biomarker of salinity and contaminant stress in mangrove crab Ucides occidentalis - Kim Pham; Andrée De Cock; Long Ho; Claudio Peter D'Incal; Wim Vanden Berghe; Dominguez Granda Luis; Filip M.G. Tack; Pieter Spanoghe; Peter L.M. Goethals (Marine Pollution Bulletin, 2026)

Agricultural and urban land use intensifies riverine GHG emissions across continents - Diego Panique-Casso; Samuel Bodé; Matti Barthel; Seid Tiku Mereta; Thu Huong Thi Hoang; Ruben Jerves-Cobo; Pascal Boeckx; Johan Six; Peter Goethals; Long Ho (Water Research, 2026)

Plastic clean-up mechanisms: Experimental insights on their bycatch - Giulia Leone; Ana I. Catarino; Ine Pauwels; Mattias Bossaer; Regine Conda Oco; Chia-Yu Chu; Peter Troch; Peter L.M. Goethals; Gert Everaert (Marine Pollution Bulletin, 2026)

Unveiling the important roles of sludge worms (Tubifex tubifex) in wetland carbon and nitrogen cycling: Implications for greenhouse gas emissions in a warming climate - Long Ho; Kim Pham; Andries Debognies; Samuel Bodé; Pieter Vermeir; Pascal Boeckx; Jo De Vrieze; Peter Goethals (Water Research, 2026)

Effects of climate change on the metabolic ecology of small yellow croaker (Larimichthys polyactis) based on dynamic energy budget (DEB) model - Xiaolin Chen; Jie Yin; Yehui Song; Fengjiao Song; Binduo Xu; Chongliang Zhang; Yupeng Ji; Yiping Ren; Long Ho; Marie Anne Eurie Forio; Peter Goethals; Ying Xue (Marine Environmental Research, 2026)

Bridging the gap in riverine greenhouse gas research: From monitoring methods to mechanistic understanding - Long Ho; Matti Barthel; Samuel Bodé; Diego Panique-Casso; Johan Six; Pascal Boeckx; Peter Goethals (Journal of Environmental Management, 2026)

Enhanced crop calibration for SWAT+: evaluating water, sediment and nutrient impacts across ten European catchments - Mikołaj Piniewski; Natalja Čerkasova; Svajunas Plunge; Michael Strauch; Christoph Schürz; Péter Braun; Enrico Antonio Chiaradia; Joana Eichenberger; Mohammad Reza Eini; Csilla Farkas; Marie Anne Eurie Forio; Peter Goethals; et al. (Environmental Modelling & Software, 2026)

Recovering European River Invertebrate Communities Homogenize or Differentiate Depending on Anthropogenic Stress - Daniela Cortés‐Guzmán; Diana E. Bowler; Marie Anne Eurie Forio; Peter Goethals; Ioannis Karaouzas; Ariane Moulinec; James S. Sinclair; Rudy Vannevel; Peter Haase; Ellen A. R. Welti (Global Change Biology, 2026)
Biodiversity loss can lead to biotic homogenization, whereby local communities within a region become increasingly similar over time, resulting in simplified communities with reduced functionality. However, our understanding of whether alleviating anthropogenic stress can reverse homogenization and promote biotic differentiation (i.e., increasing dissimilarity) remains limited, partly because the effectiveness of conservation actions is often assessed only at the local scale (e.g., increases in local diversity). Here, we examined evidence for biotic differentiation in European river invertebrate communities, a system that has generally shown signs of local recovery. We analyzed 447 time series of river invertebrate communities from 1994 to 2023, spanning 48 river basins across 15 European countries. We then related trends in community similarity within each basin, measured as taxonomic and trait β‐diversity, to spatial gradients of anthropogenic stress, including ecological quality (a proxy of general anthropogenic stress), air temperature increase, and land cover pressure. β‐diversity trends were strongly mediated by anthropogenic stress levels, with communities in lower‐stress basins showing differentiation, while those in higher‐stress basins homogenized. In addition, we found that the direction of β‐diversity change depended less on taxa or traits being gained or lost, and more on the identity of the traits involved, highlighting how trait composition mediates community responses to anthropogenic change. Specifically, additions promoted differentiation at lower stress levels but contributed to homogenization under conditions of higher stress, whereas subtractions exhibited the inverse pattern. Our results demonstrate that β‐diversity responds asymmetrically to spatial variation in anthropogenic stress, with both homogenization and differentiation occurring within a system that is, overall, undergoing recovery. Recognizing the stress‐dependent responses of β‐diversity allows researchers and managers to more accurately assess conservation success and provide recommendations that promote long‐term ecosystem structural and functional recovery.

A multivariate copula framework quantifies the augmenting joint risks of compound high temperature and dry/wet events under climate change in China - Min Liu; Tao Li; Peter Goethals; Fengjiao Song; Jianying Ma; Wei Sun (Journal of Hydrology, 2025)

Distinct pesticide profiles in sediments and red mangrove crabs (Ucides occidentalis): Impact of land use in a tropical estuary - Kim Pham; Andrée De Cock; Long Ho; Luis Dominguez Granda; Wim Vanden Berghe; Pieter Spanoghe; Peter L.M. Goethals (Environmental Pollution, 2025)

Patterns of pharmaceutical contamination in streams of European cities across urbanisation gradients: Potential impacts on One Health - Fernanda Rodrigues; Ana R. Calapez; André M.P.T. Pereira; Liliana J.G. Silva; Andreia Freitas; Rayan Bouchali; Andree De Cock; Marie Anne Eurie Forio; Peter Goethals; Silje H. Henni; Adeline Loyau; Anne Moen; et al. (Journal of Hazardous Materials, 2025)

Consumer health risk assessment of per- and polyfluoroalkyl substances (PFAS) and polycyclic aromatic hydrocarbon (PAH) in the Ecuadorian red mangrove crab - Andrée De Cock; Kaat De Clercq; Emma Pensaert; Thimo Groffen; Liesbeth Jacxsens; Luis Dominguez-Granda; Lieven Bervoets; Peter Goethals (Food Chemistry, 2025)

Interplay between temperature and redox conditions regulates wetland biogeochemistry and greenhouse gas emissions - Long Ho; Kim Pham; Andries Debognies; Samuel Bodé; Pieter Vermeir; Pascal Boeckx; Jo De Vrieze; Peter Goethals (Science of The Total Environment, 2025)

Characterization and Attribution of Historical Extreme Cold Events in China-Pakistan Economic Corridor - Tao Li; Jiayu Bao; Fengjiao Song; Philippe De Maeyer; Anming Bao; Peter Goethals (Chinese Geographical Science, 2025)

Integrated control of seafood safety and quality beyond farm-to-fork: AI-related opportunities and challenges - Andrée De Cock; Marie Anne Eurie Forio; Henry H. Hansen; Liesbeth Jacxsens; Carl Lachat; Peter Goethals (Trends in Food Science & Technology, 2025)

Chemical and microbiological analysis of urban and associated natural water systems of inhabited volcanic islands of the Galapagos (Ecuador) - Lenin Riascos-Flores; Long Ho; Wout Van Echelpoel; Marie Anne Eurie Forio; Stijn Bruneel; Niels De Troyer; Nancy de Saeyer; Rafael Bermudez; Wim Vanden Berghe; Luis Dominguez-Granda; Pascal Boeckx; Christine Van der heyden; et al. (Water Research, 2025)

The role of mangroves in early-life trophic interactions supporting fishery production in the Galapagos - José Pontón-Cevallos; Anna-Maria Vafeiadou; Nicolas Moity; Jorge Ramírez-González; María José Rendón; Mercy J. Borbor-Cordova; Tom Moens; Jorge R. Bermudez-Monsalve; Peter Goethals (Frontiers in Marine Science, 2025)
Mangrove nurseries are crucial for fishery production, supplying energy and nutrients via leaf organic matter in food webs. Recent stable isotope studies emphasize the nutritional value of mangrove detritus, especially for leaf-eating crabs, while algae remain important for other consumers in the ecosystem. In the Galapagos Islands, protected shorelines with mature mangrove forests may significantly contribute to secondary production. In this study, we measured carbon (δ¹³C) and nitrogen (δ¹ 5 N) stable isotope ratios from primary producers (e.g., mangroves, epiphytes, benthic algae), coastal sediments, and consumers (including fish larvae, epibenthic, and zooplanktonic crustaceans). We used Bayesian mixing models to assess the relative importance of food sources across six protected shorelines on Santa Cruz and Isabela Islands, representing different biogeographic origins. We also examined environmental drivers and habitat conditions influencing spatial variation in resource partitioning among consumers. Our results reveal distinct dietary patterns: ‘δ¹³C-depleted’ consumers (e.g., crab larvae, post-flexion fish larvae) relied heavily on mangroves and epiphytes, with terrestrial inputs exceeding 25%; whereas ‘δ¹³C-enriched’ consumers (e.g., polychaetes, caridean shrimps) primarily fed on microphytobenthos, macroalgae, and ¹³C-rich organic matter, with terrestrial inputs < 25%. Opportunistic feeding is suggested for fishery-related taxa, such as spiny lobster larvae. Turbidity and nitrate concentration emerged as key drivers of resource partitioning, with spatial patterns more distinct within islands than between them. These results highlight the dominant role of local hydrophysical conditions and water quality in shaping mangrove nursery functions, surpassing the influence of broader regional factors. Our study also underscores the importance of internal nutrient recycling—particularly mediated by larval crabs—in sustaining early life stages of fish and other mid-trophic species. These findings call for a deeper understanding of how habitat conditions and environmental variability influence food availability at both local and regional scales.

Fine-scale spatial and temporal dynamics of subtidal reef fish assemblages and implications for monitoring - Stijn Bruneel; José Ponton-Cevallos; Lenin Riascos; Wout Van Echelpoel; Long Ho; Andrea Mishell Rosado-Moncayo; Rebeca Parra; Rafael Bermudez; Peter Goethals (Journal of Experimental Marine Biology and Ecology, 2025)

How do varying nitrogen fertilization rates affect crop yields and riverine N2O emissions? A hybrid modeling study - Diego Panique-Casso; Nelson F. Pacheco-Bueno; Marie Anne Eurie Forio; Peter Goethals; Long Ho (Water Research, 2025)

The impacts of alien species on river bioassessment - Maria João Feio; Janine P. da Silva; Robert M. Hughes; Francisca C. Aguiar; Carlos B.M. Alves; Sebastian Birk; Marcos Callisto; Marden S. Linares; Diego R. Macedo; Paulo S. Pompeu; Wayne Robinson; Christian Schürings; et al. (Journal of Environmental Management, 2025)

Proactive policies are the key to reversing desertification in the main stream of the Tarim River in the past 30 years - Bochao Cui; Guangyan Wang; Guanghui Wei; Dongwei Gui; Sameh Kotb Abd-Elmabod; Peter Goethals; Zeeshan Ahmed (Journal of Environmental Management, 2024)

Unravelling CH4 and N2O dynamics in tidal wetlands using natural abundance isotopes and functional genes - Long Ho; Kim Pham; Matti Barthel; Stephen Harris; Samuel Bodé; Jo De Vrieze; Pieter Vermeir; Johan Six; Pascal Boeckx; Peter Goethals (Soil Biology and Biochemistry, 2024)

Regulating greenhouse gas dynamics in tidal wetlands: Impacts of salinity gradients and water pollution - Long Ho; Matti Barthel; Kim Pham; Samuel Bodé; Carl Van Colen; Tom Moens; Johan Six; Pascal Boeckx; Peter Goethals (Journal of Environmental Management, 2024)

Effect of agriculture on surface water quantity and quality in Gilgel Gibe watershed, southwestern Ethiopia - Selamawit Negassa Chawaka; Pieter Boets; Seid Tiku Mereta; Peter L. M. Goethals; Venkata Ramayya Ancha (Environmental Monitoring and Assessment, 2024)

Modeling greenhouse gas emissions from riverine systems: A review - Diego G. Panique-Casso; Peter Goethals; Long Ho (Water Research, 2024)

Unravelling spatiotemporal N2O dynamics in an urbanized estuary system using natural abundance isotopes - Long Ho; Matti Barthel; Stephen Harris; Kaat Vermeulen; Johan Six; Samuel Bodé; Pascal Boeckx; Peter Goethals (Water Research, 2023)

Impact of salinity gradient, water pollution and land use types on greenhouse gas emissions from an urbanized estuary - Long Ho; Matti Barthel; Diego Panique-Casso; Kaat Vermeulen; Stijn Bruneel; Xingzhen Liu; Samuel Bodé; Johan Six; Pascal Boeckx; Peter Goethals (Environmental Pollution, 2023)

Epigenetic analytical approaches in ecotoxicological aquatic research - Kim Pham; Long Ho; Claudio Peter D'Incal; Andrée De Cock; Wim Vanden Berghe; Peter Goethals (Environmental Pollution, 2023)

Pesticide concentration in three selected fish species and human health risk in the Lake Tana sub-basin, Ethiopia - Wondie Zelalem; Wassie Anteneh; Minwyelet Mingist; Mulugeta Kibret; Enyew Adgo; Felegush Erarto; Jasmine De Rop; Andrée De Cock; Pieter Spanoghe; Peter L. M. Goethals; Jan Nyssen; Elie Verleyen; et al. (Environmental Monitoring and Assessment, 2023)

The faunal Ponto-Caspianization of central and western European waterways - Ismael Soto; Ross N. Cuthbert; Anthony Ricciardi; Danish A. Ahmed; Florian Altermatt; Ralf B. Schäfer; Gaït Archambaud-Suard; Núria Bonada; Miguel Cañedo-Argüelles; Zoltán Csabai; Thibault Datry; Jaimie T. A. Dick; et al. (Biological Invasions, 2023)
As alien invasive species are a key driver of biodiversity loss, understanding patterns of rapidly changing global species compositions depends upon knowledge of invasive species population dynamics and trends at large scales. Within this context, the Ponto-Caspian region is among the most notable donor regions for aquatic invasive species in Europe. Using macroinvertebrate time series collected over 52 years (1968–2020) at 265 sites across 11 central and western European countries, we examined the occurrences, invasion rates, and abundances of freshwater Ponto-Caspian fauna. We examined whether: (i) successive Ponto-Caspian invasions follow a consistent pattern of composition pioneered by the same species, and (ii) Ponto-Caspian invasion accelerates subsequent invasion rates. In our dataset, Ponto-Caspian macroinvertebrates increased from two species in 1972 to 29 species in 2012. This trend was parallelled by a non-significant increasing trend in the abundances of Ponto-Caspian taxa. Trends in Ponto-Caspian invader richness increased significantly over time. We found a relatively uniform distribution of Ponto-Caspian macroinvertebrates across Europe without any relation to the distance to their native region. The Ponto-Caspian species that arrived first were often bivalves (46.5% of cases), particularly Dreissena polymorpha , followed secondarily by amphipods (83.8%; primarily Chelicorophium curvispinum and Dikerogammarus villosus ) . The time between consecutive invasions decreased significantly at our coarse regional scale, suggesting that previous alien establishments may facilitate invasions of subsequent taxa. Should alien species continue to translocate from the Ponto-Caspian region, our results suggest a high potential for their future invasion success highly connected central and western European waters. However, each species’ population may decline after an initial ‘boom’ phase or after the arrival of new invasive species, resulting in different alien species dominating over time.

Individual based models for the simulation of fish movement near barriers: Current work and future directions - Rachel Mawer; Ine S. Pauwels; Stijn P. Bruneel; Peter L.M. Goethals; Ianina Kopecki; Jelger Elings; Johan Coeck; Matthias Schneider (Journal of Environmental Management, 2023)

Mapping linkages between ecosystem services and agricultural and landscape management using structural topic modeling of scientific literature - Gonzalo Villa-Cox; Santiago J. Bucaram-Villacís; Peter Goethals; Stijn Speelman (Ecosystem Services, 2023)

Health risk-benefit assessment of the commercial red mangrove crab: Implications for a cultural delicacy - Andrée De Cock; Marie Anne Eurie Forio; Siska Croubels; Luis Dominguez-Granda; Liesbeth Jacxsens; Carl Lachat; Heydi Roa-López; Jenny Ruales; Victoria Scheyvaerts; Michelle Carolina Solis Hidalgo; Pieter Spanoghe; Filip M.G. Tack; et al. (Science of The Total Environment, 2023)

The nutritional quality of the red mangrove crab (Ucides occidentalis), harvested at two reserves in the Guayas estuary - Andrée De Cock; Marie Anne Eurie Forio; Bruno De Meulenaer; Filip Tack; Luis Dominguez-Granda; Peter L.M. Goethals (Food Chemistry, 2023)

Widespread triazole pesticide use affects infection dynamics of a global amphibian pathogen - Andrea Barbi; Tess Goessens; Diederik Strubbe; Arne Deknock; Robby Van Leeuwenberg; Niels De Troyer; Elin Verbrugghe; Mark Greener; Siegrid De Baere; Luc Lens; Peter Goethals; An Martel; et al. (Ecology Letters, 2023)
The sixth mass extinction is a consequence of complex interplay between multiple stressors with negative impact on biodiversity. We here examine the interaction between two globally widespread anthropogenic drivers of amphibian declines: the fungal disease chytridiomycosis and antifungal use in agriculture. Field monitoring of 26 amphibian ponds in an agricultural landscape shows widespread occurrence of triazole fungicides in the water column throughout the amphibian breeding season, together with a negative correlation between early season application of epoxiconazole and the prevalence of chytrid infections in aquatic newts. While triazole concentrations in the ponds remained below those that inhibit growth of Batrachochytrium dendrobatidis , they bioaccumulated in the newts' skin up to tenfold, resulting in cutaneous growth‐suppressing concentrations. As such, a concentration of epoxiconazole, 10 times below that needed to inhibit fungal growth, prevented chytrid infection in anuran tadpoles. The widespread presence of triazoles may thus alter chytrid dynamics in agricultural landscapes.

ESO-ESSO-ESTRO Multidisciplinary Course in Oncology for Medical Students: 4 Years of Experience (2016–2019) - Nicholas Pavlidis; Radoslaw Madry; Marc Peeters; Sergio Sandrucci; Janina Markowska; Fedro Peccatori; Alberto Costa; Jesper Grau Eriksen; Umberto Ricardi; Richard Poetter; Drisk Schrijvers; Jan B. Vermorken; et al. (Journal of Cancer Education, 2022)

Invasion impacts and dynamics of a European‐wide introduced species - Phillip J. Haubrock; Danish A. Ahmed; Ross N. Cuthbert; Rachel Stubbington; Sami Domisch; Jaime R. G. Marquez; Ayah Beidas; Giuseppe Amatulli; Jens Kiesel; Longzhu Q. Shen; Ismael Soto; David G. Angeler; et al. (Global Change Biology, 2022)
Globalization has led to the introduction of thousands of alien species worldwide. With growing impacts by invasive species, understanding the invasion process remains critical for predicting adverse effects and informing efficient management. Theoretically, invasion dynamics have been assumed to follow an “invasion curve” (S‐shaped curve of available area invaded over time), but this dynamic has lacked empirical testing using large‐scale data and neglects to consider invader abundances. We propose an “impact curve” describing the impacts generated by invasive species over time based on cumulative abundances. To test this curve's large‐scale applicability, we used the data‐rich New Zealand mud snail Potamopyrgus antipodarum , one of the most damaging freshwater invaders that has invaded almost all of Europe. Using long‐term (1979–2020) abundance and environmental data collected across 306 European sites, we observed that P. antipodarum abundance generally increased through time, with slower population growth at higher latitudes and with lower runoff depth. Fifty‐nine percent of these populations followed the impact curve, characterized by first occurrence, exponential growth, then long‐term saturation. This behaviour is consistent with boom‐bust dynamics, as saturation occurs due to a rapid decline in abundance over time. Across sites, we estimated that impact peaked approximately two decades after first detection, but the rate of progression along the invasion process was influenced by local abiotic conditions. The S‐shaped impact curve may be common among many invasive species that undergo complex invasion dynamics. This provides a potentially unifying approach to advance understanding of large‐scale invasion dynamics and could inform timely management actions to mitigate impacts on ecosystems and economies.

Fishers’ Local Ecological Knowledge to Support Mangrove Research in the Galapagos - José Pontón-Cevallos; Nathaly Ramírez-Valarezo; Mireya Pozo-Cajas; Gabriela Rodríguez-Jácome; Gabriela Navarrete-Forero; Nicolas Moity; Gonzalo Villa-Cox; Jorge Ramírez-González; María José Barragán-Paladines; Jorge R. Bermúdez-Monsalve; Peter L. M. Goethals (Frontiers in Marine Science, 2022)
Mangroves provide multiple ecosystem services to coastal communities and their fisheries. In the Galapagos, mangroves have been primarily prized for their role as nursery grounds; though, the importance of cultural benefits, including the development of knowledge systems among fishers, needs to be further explored. Fishers’ local ecological knowledge (LEK) has been employed in the past to answer questions about the marine environment; not yet about mangroves. In such regard, this ethnoecological approach can contribute to unveil mangrove habitat-dependence relationships among fishery taxa across the life cycle, connectivity among habitats, and productivity spatial patterns across the archipelago. To access fishers’ LEK, we conducted 35 semi-structured interviews and 2 facilitated community workshops comprising 3 activities. A photo-elicitation method allowed us to extract values given to mangroves (i.e., ecosystem services), from which indirect use values were considered more relevant for fisheries. As such, the accumulation of LEK might have been crucial for the establishment of these values among fishers. By using a species-habitat association method, we revealed a high perceived connectivity between mangroves and other coastal and marine habitats in the Galapagos. Although this suggests an overall weak dependence to the ecosystem, fishers’ anecdotes allowed us to recognize novel species occurrences and exclusive habitat uses (e.g., spawning in Centropomus viridis ). By applying Social Network Analysis to species-habitat association results, we learned that certain migratory commercial species (e.g., Lutjanus argentiventris , Seriola rivoliana ) might constitute critical links in marine trophic webs and across seascapes. Finally, through scoring and participatory mapping methods, we revealed the prominence of western islands’ mangroves for fishery productivity, which were linked to biophysical attributes, like forest canopy and freshwater. Yet, other locations in central and southeastern islands might also be important, as they hold similar attributes. Interviews to other mangrove users (e.g., naturalist guides, park rangers, scientists; N = 33), and past scientific studies allowed us to triangulate LEK and to find complementarity among knowledge sources. Despite having an explorative focus, our work already showcases the potential of fishers’ LEK in improving mangrove research in the Galapagos, and the arising opportunities for ecosystem-based fisheries management and mangrove protection.

Greenhouse gas dynamics in an urbanized river system: influence of water quality and land use - Long Ho; Ruben Jerves-Cobo; Matti Barthel; Johan Six; Samuel Bode; Pascal Boeckx; Peter Goethals (Environmental Science and Pollution Research, 2022)

Cover Image - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)

A global agenda for advancing freshwater biodiversity research - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)
Global freshwater biodiversity is declining dramatically, and meeting the challenges of this crisis requires bold goals and the mobilisation of substantial resources. While the reasons are varied, investments in both research and conservation of freshwater biodiversity lag far behind those in the terrestrial and marine realms. Inspired by a global consultation, we identify 15 pressing priority needs, grouped into five research areas, in an effort to support informed stewardship of freshwater biodiversity. The proposed agenda aims to advance freshwater biodiversity research globally as a critical step in improving coordinated actions towards its sustainable management and conservation.

Assessing the Drivers behind the Structure and Diversity of Fish Assemblages Associated with Rocky Shores in the Galapagos Archipelago - Stijn Bruneel; Wout Van Echelpoel; Long Ho; Heleen Raat; Amber Schoeters; Niels De Troyer; Ratha Sor; José Ponton-Cevallos; Ruth Vandeputte; Christine Van der heyden; Nancy De Saeyer; Marie Anne Eurie Forio; et al. (Journal of Marine Science and Engineering, 2021)
Oceanic islands harbor unique yet fragile marine ecosystems that require evidence-based environmental management. Among these islands, the Galapagos archipelago is well known for its fish diversity, but the factors that structure communities within and between its islands remain poorly understood. In this study, water quality, physical habitats and geographical distance were assessed as potential predictors for the diversity and structure of fish assemblages. Differences in the structure of fish assemblages of the two studied islands (Santa Cruz and Floreana) were most likely driven by temperature and nutrient concentrations. In the relatively highly populated island Santa Cruz, the structure of fish assemblages was more affected by water conditions than physical habitats while the contrary was true for the more pristine area of Floreana. A wide variety of species with different geographical origins were distributed over the different islands, which indicates that most fish species are able to reach the islands of the archipelago. However, temperature gradients and elevated nutrient levels cause large differences in the structure of local fish assemblages. In addition, in Santa Cruz nutrient concentrations were negatively correlated with α diversity. Since pollution is a clear pressure on the fish assemblages of oceanic islands, environmental management of the coastal areas is of paramount importance.

Intra- and intercontinental variation in the functional responses of a high impact alien invasive fish - Pieter Boets; Ciaran Laverty; Shinji Fukuda; Hugo Verreycken; Kyle Green; Robert J. Britton; Joe Caffrey; Peter L. M. Goethals; Josephine Pegg; Vincent Médoc; Jaimie T. A. Dick (Biological Invasions, 2019)

Using Macroinvertebrates and Birds to Assess the Environmental Status of Wetlands across Different Climatic Zones in Southwestern Ethiopia - Selamawit Negassa Chawaka; Pieter Boets; Seid Tiku Mereta; Long T. Ho; Peter L. M. Goethals (Wetlands, 2018)

Preparation and Characterization of Alginate Microparticles Containing a Model Protein for Oral Administration in Gnotobiotic European Sea Bass (Dicentrarchus labrax) Larvae - Eamy Nursaliza Yaacob; Jens Goethals; Aline Bajek; Kristof Dierckens; Peter Bossier; Bruno G. De Geest; Daisy Vanrompay (Marine Biotechnology, 2017)

River Water Pollution Status and Water Policy Scenario in Ethiopia: Raising Awareness for Better Implementation in Developing Countries - Aymere Awoke; Abebe Beyene; Helmut Kloos; Peter L.M. Goethals; Ludwig Triest (Environmental Management, 2016)

The distribution of an invasive fish species is highly affected by the presence of native fish species: evidence based on species distribution modelling - Pieterjan Verhelst; Pieter Boets; Gerlinde Van Thuyne; Hugo Verreycken; Peter L. M. Goethals; Ans M. Mouton (Biological Invasions, 2016)

Integrating data-driven ecological models in an expert-based decision support system for water management in the Du river basin (Vietnam) - Thu Huong Hoang; Ans Mouton; Koen Lock; Niels De Pauw; Peter L. M. Goethals (Environmental Monitoring and Assessment, 2013)

A comparison of the short-term toxicity of cadmium to indigenous and alien gammarid species - Pieter Boets; Koen Lock; Peter L. M. Goethals; Colin R. Janssen; Karel A. C. De Schamphelaere (Ecotoxicology, 2012)

Integrated Constructed Wetlands (ICW): Ecological Development in Constructed Wetlands for Manure Treatment - Pieter Boets; Evi Michels; Erik Meers; Koen Lock; Filip M. G. Tack; Peter L. M. Goethals (Wetlands, 2011)

Did global warming and alien invasions affect surf zone hyperbenthic communities on sandy beaches in Belgium? - Koen Lock; Jan Mees; Magda Vincx; Peter L. M. Goethals (Hydrobiologia, 2011)

Using long-term monitoring to investigate the changes in species composition in the harbour of Ghent (Belgium) - Pieter Boets; Koen Lock; Peter L. M. Goethals (Hydrobiologia, 2011)

Impact of habitat diversity on the sampling effort required for the assessment of river fish communities and IBI - Chris Van Liefferinge; Ilse Simoens; Christian Vogt; Tom J. S. Cox; Jan Breine; Dirk Ercken; Peter Goethals; Claude Belpaire; Patrick Meire (Hydrobiologia, 2010)

Selecting Variables for Habitat Suitability of Asellus (Crustacea, Isopoda) by Applying Input Variable Contribution Methods to Artificial Neural Network Models - Ans M. Mouton; Andy P. Dedecker; Sovan Lek; Peter L. M. Goethals (Environmental Modeling & Assessment, 2010)

Special issue ‘Ecological informatics applications in water management’ - Peter L. M. Goethals (Aquatic Ecology, 2007)

Applications of artificial neural networks predicting macroinvertebrates in freshwaters - Peter L. M. Goethals; Andy P. Dedecker; Wim Gabriels; Sovan Lek; Niels De Pauw (Aquatic Ecology, 2007)

Analysis of macrobenthic communities in Flanders, Belgium, using a stepwise input variable selection procedure with artificial neural networks - Wim Gabriels; Peter L. M. Goethals; Andy P. Dedecker; Sovan Lek; Niels De Pauw (Aquatic Ecology, 2007)

Decision Tree Models for Prediction of Macroinvertebrate Taxa in the River Axios (Northern Greece) - Eleni Dakou; Tom D’heygere; Andy P. Dedecker; Peter L. M. Goethals; Maria Lazaridou-Dimitriadou; Niels De Pauw (Aquatic Ecology, 2007)

Development of an in-stream migration model for Gammarus pulex L. (Crustacea, Amphipoda) as a tool in river restoration management - Andy P. Dedecker; Peter L. M. Goethals; Tom D’heygere; Niels De Pauw (Aquatic Ecology, 2006)

Application Of Artificial Neural Network Models To Analyse The Relationships Between Gammarus pulex L. (Crustacea, Amphipoda) And River Characteristics - Andy P. Dedecker; Peter L. M. Goethals; Tom D'heygere; Muriel Gevrey; Sovan Lek; Niels De Pauw (Environmental Monitoring and Assessment, 2005)

A fish-based index of biotic integrity for upstream brooks in Flanders (Belgium) - Jan Breine; Ilse Simoens; Peter Goethals; Paul Quataert; Dirk Ercken; Chris Van Liefferinghe; Claude Belpaire (Hydrobiologia, 2004)